Conflictos Armados en el VRAEM - Mendoza Rodríguez, Carlos Manuel (2022)
This research work develops the conflict scenario that is currently experienced in the area known as VRAEM, with the purpose of determining if the application of International Humanitarian Law is feasible through a Non-International Armed Conflict, and if its application favors the protection of persons not participating in hostilities; determining, if it is going to regulate through the common article 3 of the conventions of Geneva or by the additional protocol II. Precisely, this need arises due to the confusion of those who participate in the hostilities, regarding whether the application of a NIAC would lead to granting an advantage to the hostile groups, or if the situation could give the prisoner of war status to the time of his capture. Likewise, the evolution of the Armed Forces and Shining Path will also be analyzed, from the beginning of the Conflict from the 1980s to our time. Following this line, the investigation starts from the premise of the evolution of the conflict in the VRAEM, and if these currently exceed the threshold of internal disturbances or those called by the doctrine as other situations of internal violence (OSVI), allowing to determine what type of regulatory framework to use, but above all with the premise of which of these is the one that provides the greatest protection to people who do not participate in hostilities.